2010
DOI: 10.1109/tns.2010.2042614
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure of Fiber Bragg Gratings in the BR1 Low-Flux Nuclear Reactor

Abstract: We report the results of a long-term exposure of fiber Bragg gratings in the BR1 low-flux nuclear reactor at SCK CEN in Mol, Belgium. Gratings fabricated in the photosensitive and the standard fibers were installed in February 2000 in a research channel of the reactor and remained there until August 2008. During this time the reactor was operational 4690h so that the gratings received a total thermal/fast neutron fluence 16 9 1 47 10 17 n/cm 2 , and a gamma-dose 10 MGy. The temperature cycled from 10 to 80 C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Moreover, the RIE phenomenon has been employed for the development of several dosimeter configurations based on radio-and thermo-luminesce effect [33][34][35][36][37]. Afterwards, many studies and reviews also targeted Fiber Bragg Grating (FBG) sensors written in several optical fibers by different techniques and irradiated under different conditions [38][39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the RIE phenomenon has been employed for the development of several dosimeter configurations based on radio-and thermo-luminesce effect [33][34][35][36][37]. Afterwards, many studies and reviews also targeted Fiber Bragg Grating (FBG) sensors written in several optical fibers by different techniques and irradiated under different conditions [38][39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…The first two are common in space, whereas neutrons are found in nuclear reactor cores or fusion-devoted facilities. Test facilities offering these types of beams are less accessible and only a few studies have been published about the FBG response under protons [ 39 , 101 , 102 , 103 , 104 , 105 ], electrons [ 104 ], or neutrons [ 19 , 22 , 23 , 24 , 27 , 28 , 106 ].…”
Section: Radiation Effects On Fbgsmentioning
confidence: 99%
“…Until today a lot of researchers have studied the gamma-radiation resistance of the gratings: it depends on several parameters, such as fiber composition, FBG inscription, pre-and post-inscription treatments (see review paper [11] for references). However, only few tests were performed in mixed gamma-neutron environment, as the nuclear reactor cores [12], [13], [14]. The grating sensitivity to mixed gamma-neutron radiation is higher than to pure gamma one and the Bragg wavelength behavior depends a lot on the neutron flux: at high value (>2·10 11 n·cm -2 ·s -1 ) B increases linearly with the dose, whereas at lower flux it shows a saturating trend [12].…”
Section: B Information Expected From the Irradiation In A Mixed Neutmentioning
confidence: 99%
“…The grating sensitivity to mixed gamma-neutron radiation is higher than to pure gamma one and the Bragg wavelength behavior depends a lot on the neutron flux: at high value (>2·10 11 n·cm -2 ·s -1 ) B increases linearly with the dose, whereas at lower flux it shows a saturating trend [12]. However, it has been demonstrated that the temperature sensitivity does not change because of the radiation [14].…”
Section: B Information Expected From the Irradiation In A Mixed Neutmentioning
confidence: 99%